Pengembangan Sistem Informasi Manajemen Registrasi Siswa Pada Bimbingan Belajar Lingua Institute - Fajar Rizki Kristiono; Issa Arwani; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Lingua Institute is one of institutions in Malang which is provide a service in education services to the people in Malang. Lingua Institute was created on purpose of helping people develop language skills, linguistic knowledge and literature in English and Arabic and assist them in translating various documents into English and Arabic. However, in its operations, Lingua Institute still experiences problems when running some of business proses. Based on the results of the initial interviews conducted with the director of Lingua Institute, it was found there was obstacles in several business processes, some of them is unclear tasks and responsibilities for employee as well business process flow in the process of registering new students, because the registration service is not only carried out by the money manager or admin, but also carried out by other employees in the Lingua Institute, such as tutors. Based on the problems, we need an information system that can manage data in order to help better business processes. In this study the development waterfall method will be used in the development of information systems. The development of informantion systems will be assisted by the PHP programming language and Laravel as a framework. Testing in this research uses the System Usability Scale and Validation Testing. The System Usability Scale test results get a value of 80 which means the system can be accepted by the user.